Dimensions, Magnitude and Personal Antecedents of Job Satisfaction Among a Slice of Health Professionals in an Egyptian Context - Abdel-Aziz, Basem (International Journal For Research In Health Sciences And Nursing, 2020)
Job Satisfaction (JS) is becoming a focus of universal extensive research. Twenty itemed Minnesota Satisfaction Questionnaire-short form (MSQ-S) has been used to explore the dimensions, magnitude and personal antecedents of JS among a slice of health professionals in an Egyptian context. The study was conducted on healthcare professionals performing their postgraduate studies at High Institute of Public Health, Alexandria University, Egypt. Four consecutive samples (S1, S2, S3, & S4) were collected one month apart. Preliminary screening revealed that all twenty items were suitable for factor analysis. Confirmatory factor analysis in an exploratory mode (ECFA) was performed on S1, S2, & S3 to explore the dimensionality of MSQ-S. The uni-, bi-, tri-, and tetra-dimensional structures showed ample internal consistency reliability (AICR), adequate global and local fit indices (AGLFI), and sufficient discriminant validity when applicable (SDVWA). However, an index of convergent validity [average variance extracted (AVE)] was suboptimal. Based on substantive and empirical reasons four "problematic" items were removed from the measuring instrument. Datasets S1, S2, & S3 were employed to explore the dimensionality of the 16-itemed refined instrument. The refined uni-, bi-, tri-, and tetra-dimensional models showed AICR, AGLFI, and SDVWA. However, AVE was suboptimal for the refined uni-, tri-, and tetra-dimensional and marginally tolerable for the refined bidimensional model (M2R). Confirmatory factor analysis was employed on S4 to confirm M2R which displayed acceptable reliability and construct validity. M2R was utilized to measure JS in S1 revealing that more than 70% were moderately satisfied with overall JS and its two dimensions. Analysis of 16 facets of MSQ-S showed that payment and work conditions were the most problematic aspects. No association has been displayed between overall JS and participants' personal characteristics, except gender as males displayed higher level of JS than females. Recommendations, managerial implications, future research directions, and limitations have been underscored.